Study on water savings through reuse of rainwater (Research, Society and Development, 2023)
Water is an essential natural resource for life on the planet, whether as a biochemical component of living beings, as a means of life for various plant and animal species, as a representative element of social and cultural values and even as a production factor for various goods. final and intermediate consumption. However, the growing population has increased the demand for this good. On the other hand, the supply of potable water becomes increasingly scarce to meet the diverse needs of the population. Given this scenario, it is essential to implement methodologies that enhance the rational use of water. Water resources come from various natural sources, such as aquifers, groundwater and rivers, essentially for the existence of all living beings, which is the essential reason why society is increasingly concerned with the availability of water. fresh water on our planet. Therefore, it is necessary to study ways to reuse rainwater as a way to save and preserve drinking water. In this research work, a study was carried out on the feasibility of using rainwater throughout the country, taking into account the differences in rainfall. Thus, for this purpose, it was necessary to identify the rainfall regime of the different Brazilian capitals through the National Institute of Meteorology (INMET) database, determine the volumes of rainwater reservoirs for each situation and evaluate the influence of the rainfall regime on the potential for rainwater harvesting.